Chronic obstructive pulmonary disease and COVID-19: interrelationships. Issue 2 (March 2022) - Singh, Dave; Mathioudakis, Alexander G.; Higham, Andrew
Abstract : Purpose of review: Chronic obstructive pulmonary disease (COPD) and COVID-19 have many potentially negative interrelationships, which may influence the course of infection and clinical outcomes. The aim of this review is to provide clinicians with an up-to-date perspective of the complex interactions between COPD and COVID-19. Recent findings: We consider mechanisms that could increase SARS-CoV-2 infection susceptibility in COPD, including increased ACE2 expression, reduced antiviral defence and dysfunctional immunity. We review evidence that COPD is associated with worse clinical outcomes from COVID-19 in analyses that have adjusted for confounding factors, and describe the mechanisms responsible. We discuss the use of inhaled corticosteroids in the context of susceptibility to COVID-19, and consider the impact of COVID-19 on the usual care of COPD patients. Summary: The current review highlights the evidence that COPD patients have worse outcomes from COVID-19, and the multiple mechanisms responsible.